2020
DOI: 10.2147/ott.s250066
|View full text |Cite
|
Sign up to set email alerts
|

<p>PSAT1 Regulated Oxidation-Reduction Balance Affects the Growth and Prognosis of Epithelial Ovarian Cancer</p>

Abstract: Introduction: A growing number of studies have found that the serine-glycine biosynthesis pathway is highly activated for biosynthesis in cancer progression and metastasis. Phosphoserine aminotransferase 1 (PSAT1) catalyzes the second step of the serine-glycine biosynthesis pathway; the effects and mechanism of PSAT1 in epithelial ovarian cancer (EOC) remains unclear. Materials and Methods: The expression of PSAT1 in clinical EOC samples and normal ovarian tissues was conducted by RT-PCR, Western blot, and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Ovarian cancer, a type of malignancy in the ovary, is the most lethal gynaecological carcinoma as well as the fifth leading cause of cancer mortality among women [ 1 ]. Over 85% of ovarian cancers originate from the epithelium (known as epithelial ovarian cancer, EOC), with serous ovarian cancer being the most common histological subtype [ 2 ]. Currently, the main treatment options for epithelial ovarian cancer are tumour cell reduction surgery and platinum-based chemotherapy, immunotherapy, and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovarian cancer, a type of malignancy in the ovary, is the most lethal gynaecological carcinoma as well as the fifth leading cause of cancer mortality among women [ 1 ]. Over 85% of ovarian cancers originate from the epithelium (known as epithelial ovarian cancer, EOC), with serous ovarian cancer being the most common histological subtype [ 2 ]. Currently, the main treatment options for epithelial ovarian cancer are tumour cell reduction surgery and platinum-based chemotherapy, immunotherapy, and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main treatment options for epithelial ovarian cancer are tumour cell reduction surgery and platinum-based chemotherapy, immunotherapy, and targeted therapy. Although these therapeutic options are available, the overall five-year survival rate remains low, at around 30%-40% [ 2 ]. It is estimated that 22,530 patients were diagnosed with ovarian cancer in 2019 in the United States, of which 13,980 patients died [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 31 PSAT1 is upregulated in Burkitt lymphoma via a MYC-dependent ATF4 transcription factor mechanism, and overexpression of PSAT1 is reportedly associated with poor prognoses in patients with Burkitt lymphoma, 32 nasopharyngeal carcinoma, 33 colorectal carcinoma, 34 , 35 and epithelial ovarian cancer. 36 Studies suggest that NGB may be a tumor suppressor that inhibits cell growth, cell aggregation, and tumorigenicity. 37 LAMP2 deficiency increases the risk of ferroptosis in retinal pigment epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cytochrome CYP450 cyclooxygenase can catalyze the epoxidation of unsaturated fatty acids such as arachidonic acid and that arachidonic acid-derived products can effectively promote angiogenesis of lipids and tumor development [ 14 ]. Zhang et al reported that the growth and prognosis of cancer can be regulated by affecting the balance of redox reactions [ 15 ]. These findings support our enrichment analysis results.…”
Section: Discussionmentioning
confidence: 99%